Pemahaman Tekstual Dan Kontekstual Terhadap Sunnah Nabi (Studi Kritis atas Pemikiran Syaikh Muhammad Al-Gazali) - Syam, Masiyan Makmum (Al-Hikmah Journal for Religious Studies, 2014)
Hadis is regarded as the second source of Islam beside al-Quran. Most of Moslems believe that thousands of hadis collected in some hadis books were originally words of Muhammad saw. Itâs Muhammad al- Gazali who reaffirmed the originality of hadis. In his opinion, hadis should be seen in two aspect; texts and context. According to al-Gazali, many of muhaddisun ignored these aspects. Thus, the meaning of hadis lost its moral force and tends to be textual. Therefore the spirit of hadis sometimes is not relevant with current issues. For this reason al-Gazali explored and examined the originality of matan. In his opinion, hadis cannot be categorized shahih if its contents are again the Qurâani messages.